Long term oviposition preference and larval performance of Schizomyia macrocapillata (Diptera: Cecidomyiidae) on larger shoots of its host plant Bauhinia brevipes (Fabaceae) - Santos, Jean Carlos; Silveira, Fernando A. O; Fernandes, G. Wilson (Evolutionary ecology, 2008)
The Plant Vigor Hypothesis (PVH) proposes that natural selection on female oviposition choice results from higher fitness of larvae on more vigorous and larger plant modules. For six consecutive years we tested the PVH predictions by investigating the effect of shoot size of Bauhinia brevipes (Fabaceae) on the oviposition preference and offspring survival of the gall-midge Schizomyia macrocapillata (Diptera: Cecidomyiidae). Additionally, we analyzed the effects of bottom-up and top-down mortality forces on the system. The hypersensitive reaction (bottom-up effect) accounted for more than 90% larval mortality of S. macrocapillata, making available few galls to be found and killed by natural enemies (top-down effect). Smaller shoots were always more abundant while longer shoots were rare. Nevertheless, the percent number of galls induced by S. macrocapillata was up to 10-fold greater on the largest shoots, corroborating the preference prediction of the PVH. Schizomyia macrocapillata should use over-exploit larger shoots to maximize the preference for, and consequently increase the performance on these shoots. Our results partially support the performance prediction of the PVH: (1) the observed survival was higher than expected on longer shoots, and (2) the ratio of survival per shoot was positively related with shoot length only in 2 years. Thus, we found a link between female preference and larval performance on large-sized shoots, at least in some years. The gall-midge attack pattern in this study might be an evolved response to maximize the female preference and increased larval performance on longer shoots of the host plant.